The economic culture of the polish countryside in the process of 9. changes – an outline of the issues - Krzyminiewska, Grażyna (Ekonomika, 2020)
The paper The Economic culture of the Polish countryside in the Process of Changes – an outline of issues sets up a thesis that the transformation process has a multidimensional character and that its final effect is decided by an interaction between the organizational-institutional and mental-cultural level. Drawing attention to the cultural aspect increases the accuracy of the formulated diagnoses, explanations and prognoses. The author’s arguments are based on three elements. Firstly, she indicates the theoretical aspects of understanding the economic culture – the ways of defining and operation; secondly, she discusses the essential components of the traditional economic culture of the countryside, indicating the impact that the traditional value system has on contemporary economic attitudes and mentality. Thirdly, she points out how the changes connected with the transformation process exert an influence on modification of the crucial elements of this culture, adapting it to the requirements of contemporary world.
Keywords: economic culture; Polish countryside; value system